Komunikasi Budaya Berbasis Memori Kolektif dalam Pembelajaran Sejarah: Model Penguatan Historical Consciousness pada Generasi Digital - Renol Hasan; Syahrir Soleman (Jurnal Pendidikan, Sejarah, dan Budaya, 2026)
Digital transformation has changed the way the younger generation accesses, understands, and interprets history, thereby necessitating the development of learning approaches capable of connecting historical experiences with the context of contemporary life. This study aims to analyze the relationship between cultural communication, collective memory, and historical consciousness, as well as to formulate a conceptual model of history learning that is relevant to the digital generation. The study employs a non-empirical, literature-review-based method with a descriptive-analytical approach. Data sources were drawn from scholarly articles, academic books, and research findings related to cultural communication, collective memory, history education, and historical consciousness. Analysis was conducted through the identification, categorization, interpretation, and conceptual synthesis of various findings from the literature. The research results indicate that cultural communication functions as a mechanism for transmitting historical meaning, collective memory acts as a source for the formation of identity and social orientation, while historical consciousness develops through a process of reflection that connects the past, present, and future. The formulated model positions the exploration of collective memory, cultural interpretation, historical reflection, and social action orientation as key stages in strengthening historical consciousness.This model provides a theoretical foundation for the development of history education that is more contextual, reflective, and adaptive to the characteristics of the digital generation.